Analisis Pengendalian Persediaan Air Mineral Dengan Metode Just In Time - Sanny Hahury; Umar Rusli Marasabessy; Asih Ahistasari; Fadli Pelani Rama Silalahi (Universitas Muhammadiyah Sorong, 2022)
Inventory in a company has an important role in supporting the course of a production and sales process. If the inventory in a company is managed properly, the production and sales processes can run smoothly. Based on this method of meeting the needs that are applied, sometimes the inventory becomes out of control, because demand changes every time. In response to this problem, Gudang Blessing Mandiri requires a new method to control inventory to be more efficient and effective. One method of inventory control is a method that only brings in goods if they are going to do the sales process or if they have received orders from consumers or distributors. And cooperate or contract with several suppliers of goods in the long term. This method is called Just In Time (JIT). The results obtained after applying the Just In Time method to the Mandiri Berkah Warehouse, the total cost for Aqua 330 ml was Rp. 103,723 with a cost savings of Rp. 105,476, on Aqua 600 ml of Rp. 236,560 with a cost savings of Rp. 552,683 and at Aqua 1,500 ml Rp. 187,789 with a cost savings of Rp. 417,158.